KONSEP AKSESBILITAS DAN VEGETASI PADA TAMAN BERMAIN ANAK DIFABEL DI SLB-C LAWANG - Irawan Setyabudi; Wahidyanti Rahayu Hastutiningtyas; Maria Nelde Olo (BUANA SAINS, 2017)
Person with disabilities has different needs than normal individuals. This difference causes limitations in movement and orientation. As a designer, of course in creating facilities can be used all levels of society, so the need for special treatment in design. Part of architectural context other than buildings is open space. Open space has another function, as a circulation path can also be developed in the form of park. Benefits for people with disabilities, parks can also be a means of learning, training independence and therapeutic areas. In the case study selected location in SLB-C Lawang (tuna grahita or mental retardation), this location has a large area for the development of garden design of motor development and mental children with disabilities or called educational park. The park is divided into two zones: active and passive. The active zone consists of a children's playroom and a sensory park that trains the senses of the five senses, while the passive zone as a park to be visually enjoyed. Therapeutic activities for mental retardation are not just for healing but to practice the senses' abilities of smell, taste, touch, and listener. Initially still an open space that has not been functioned specifically. The problem in this research is how the concept of accessibility and vegetation so that facilities can be used. The objective of the study was to develop a system in parks that can be enjoyed by people with disabilities and as a means of therapy. The result of this research is a concept of ease of achievement of garden for children with disfigured attention to detail of circulation design and variety of vegetation that support the concept of sensory garden so as therapy area.